Losses in Each Stage of Rice Harvest and Postharvest - Lusi Andriani; Novira Kusrini; Maswadi (Institut Pertanian Bogor, 2025)
Indonesia ranks second in the world for high food loss and waste levels, totaling 300 kg per capita per year. Most of these losses occur during harvesting and post-harvest stages before the produce reaches the consumer. This research aimed to determine the correlation between these stages and production loss. The research was conducted using a descriptive quantitative method in Sungai Besar Village, Ketapang Regency, from November 2022 to February 2023. The respondents in this study were 89 farmers in the village. The results showed that each stage, including the harvesting and post-harvest stages, was correlated to yield loss. The yield loss at each stage varied greatly and is affected by several factors, including harvest age, harvesting methods, tools, rice varieties, threshing mechanisms, threshing delays, drying duration, drying medium size, grain cleaning, raw grain materials, maturity level, and milling machines. The percentage of yield loss ranges from 2 to 4.46% (in the harvesting and threshing stages), 0.52 to 1.55% (in the drying stage), and 1 to 2,5% (in the milling stage). Keywords: rice, food loss, harvester, post-harvest